Do Infant Temperament Characteristics Predict Core Academic Abilities in Preschool-Aged Children? - Gartstein, Maria A. (Learn Individ Differ, 2016)
Examined relationships between temperament, measured via parent report at 4 months and structures laboratory observations at 12 months of age, and a school readiness battery administered at about 4 years of age (N=31). Scores on the School Readiness Assessment of the Bracken Basic Concept Scale (BBCS) were related to infant Positive Affectivity/Surgency (PAS), with infants described as demonstrating higher levels of PAS at 4 months of age later demonstrating greater school readiness in the domains of color, letter, and number skills. Regulatory Capacity/Orienting (RCO) at 4 months also predicted color skills, with more regulated infants demonstrating superior pre-academic functioning in this area. Analyses involving laboratory observations of temperament provided additional information concerning the importance of infant Positive Affectivity/Surgency, predictive of overall letter skills and overall school-readiness scores later in childhood. Results are discussed in the context of implications for theory and research, as well as early education settings.